Bacterium-mimicking sequentially targeted therapeutic nanocomplexes based on O-carboxymethyl chitosan and their cooperative therapy by dual-modality light manipulation. (15th July 2021) - Zhou, Jie; Ma, Shengnan; Zhang, Yuxin; He, Yiyan; Mao, Hongli; Yang, Jun; Zhang, Hu; Luo, Kui; Gong, Qiyong; Gu, Zhongwei
Graphical abstract: Highlights: Fabrication of O -carboxymethyl chitosan-based bacterium-mimicking nanosystems. Co-delivery of TRAIL plasmids and chlorin e6 to cancer cells. Enhanced gene transfection efficiency and apoptosis via PCI and nuclear targeting. Light-enhanced gene-photodynamic therapy via dual-modality light manipulation. Abstract: An integrated gene nanovector capable of overcoming complicated physiological barriers in one vector is desirable to circumvent the challenges imposed by the intricate tumor microenvironment. Herein, a nuclear localization signals (NLS)-decorated element and an iRGD-functionalized element based on O -carboxymethyl chitosan were synthesized, mixed, and coated onto PEI/DNA to fabricate bacterium-mimicking sequentially targeted therapeutic nanocomplexes (STNPs) which were internalized through receptor-mediated endocytosis and other pathways and achieved nuclear translocation of DNA. The endo/lysosomal membrane disruption triggered by reactive oxygen species (ROS) after short-time illumination, together with the DNA nuclear translocation, evoked an enhanced gene expression. Alternatively, the excessive ROS from long-time irradiation induced apoptosis in tumor cells, bringing about greater anti-tumor efficacy owing to the integration of gene and photodynamic therapy. Overall, these results demonstrated bacterium-mimicking STNPs could be a potential candidate for tumor treatments.